Podatek liniowy a aktywność gospodarcza przedsiębiorstw - Kluzek, Marta (Proportional Tax and Enterprises' Economic Activity, 2007)
Tax competition initiated at a global scale in the 80s has started lively discussions on solutions that could be the best for individual economies development of different countries. Post-communist countries have started reforming their taxation systems by introduction, among others, proportional tax for individuals. The advantages of the change are mainly limitation of avoidance or evasion of taxes paying as well as simplification of taxation system. These, consequently, decrease administration burden and the costs of economic activity. In Poland 19% proportional tax has been introduced for enterprises since 2004. Tax-payers find this solution encouraging slice the money they have to pay for the treasury is the sum they can afford.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 304-312